Universalitas Bahasa dalam Konteks PBA li al-Marhalah al-Ibtidā’iyyah - Nanik Setyowati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2018)
This study aims to generalize the concept of the universality of language in the context of learning Arabic in Indonesia. The method used thisresearch is descriptive qualitative. Already Arabic learning at the basic level does not use conventional approaches and methods in this era, but a teachermust be more constructive in managing learning, one of them is the approach of universality of language. A good Arabic learning must have an universalityof language value. The universality language is a system of sound symbols that must be complemented by the full and systematic dimensions of language. Theprinciples which are have to be folowwed in the universality of language such as syntac, phonology, morphology and semantic principles. Thus, PBAcontestation in basic lavel using the system of language universality will be better to improve students Arabic language skills.